Produção de alérgenos recombinantes relacionados a Der p 1 de Dermatophagoides pteronyssinus com potencial aplicação na avaliação da resposta imune humoral e celular em pacientes com alergias respiratórias - Tomaz, Laura Fontes (2011)
Dermatophagoides pteronyssinus (Dp) is an important specie of house dust mite associated with allergic diseases. Allergens from Dp are important causes of sensitization and mediated responses to specific immunoglobulin E (IgE) among patients with asthma and allergic rhinitis. The aim of this study was to produce recombinant protein Der p 1 and Der p 1-related IgE binding epitopes (rDer p 1172-243) to evaluate their reactivity to IgE in the serum of mite sensitized individuals using enzyme immunoassays. The sequences of rDer p 1 and rDer p 1172-243 were amplified and subcloned into E. coli. After expression and purification the reactivity of IgE to rDer p 1 and rDer p1172-243 was determined by ELISA. The results showed that rDer p 1 expressed in E. coli presented an estimated molecular weight of about 26 kDa and rDer p 1172-243 about 8kDa. The expressed rDer p 1 protein and rDer p 1172-243 reacted positively with IgE in 88% and 84% of sera from allergic patients, respectively. However, sera from negative patients showed crossreactivity to rDer p 1, although the same was not observed for rDer p 1172-243. It can be suggested that rDer p 1172-243 are promising candidates for the diagnosis of allergy caused by D. pteronyssinus in mite sensitized patients.